REGULATIONS ON THE VALIDATION OF MARRIAGE AGREEMENTS CARRIED OUT BY NOTARIES IN INDONESIAN POSITIVE LAW FOLLOWING CONSTITUTIONAL COURT DECISION NUMBER 69/PUU-XIII/2015 - Safira Annisa; Djumikasi; Yenny Eta Widyanti (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The changes that occurred in the Constitutional Court Decision Number 69/PUU-XIII/2015 caused multiple interpretations, the change of the phrase "Making a written agreement" in Article 29 paragraph (1) of the Marriage Law to "submitting a written agreement" in the Constitutional Court Decision Number 69/PUU-XIII/2015 needs to be explained in more detail so that it creates legal certainty. The difference between the phrases "Making" and "Submitting" in the KBBI has a very different meaning, not explaining the meaning of this phrase will cause legal uncertainty, especially for Notaries. So it is necessary to study how the regulation of the ratification of marriage agreements carried out by notaries in Indonesian positive law after the Constitutional Court Decision Number 69/PUU-XIII/2015. The type of research used is the normative legal method, namely research conducted on legal sources such as laws or other literature that includes analysis of legal principles to identify and resolve legal issues that will be studied using the Theory of Legal Certainty. The results of the analysis explain that from the Constitutional Court Decision Number 69/PUU-XIII/2015, Notaries should have two new authorities.